Review of State Comprehensive Cancer Control Plans for Genomics Content - Robert C. Millikan, DVM, PhD; Tejinder Rakhra-Burris, MA; Erin Shaughnessy Zuiker, MPH; Debra E. Irwin, PhD, MSPH (Centers for Disease Control and Prevention, 2005)
Introduction The goals of this study were to determine U.S. states with Comprehensive Cancer Control plans that include genomics in some capacity and to review successes with and barriers to implementation of genomics-related cancer control initiatives. Methods This study was conducted in two phases. Phase one included a content analysis of written state Comprehensive Cancer Control plans (n = 30) for terms related to genomics, or genomic components (n = 18). The second phase involved telephone interviews with the Comprehensive Cancer Control plan coordinators in states with plans that contained genomic components (n = 16). The interview was designed to gather more detailed information about the genomics-related initiatives within the states Comprehensive Cancer Control plan and the successes with and barriers to plan implementation, as defined by each state. Results Eighteen of the 30 Comprehensive Cancer Control plans analyzed contained genomics components. We noted a large variability among these 18 plans in the types of genomics components included. Nine (56%) of the 16 states interviewed had begun to implement the genomics components in their plan. Most states emphasized educating health care providers and the public about the role of genomics in cancer control. Many states consider awareness of family history to be an important aspect of their Comprehensive Cancer Control plan. Approximately 67% of states with family history components in their plans had begun to implement these goals. Virtually all states reported they would benefit from additional training in cancer genetics and general public health genomics. Conclusion The number of states incorporating genomics into their Comprehensive Cancer Control plans is increasing. Family history is a public health application of genomics that could be implemented more fully into Comprehensive Cancer Control plans.